Strategi Pemerintah Daerah dalam Mengatasi Praktek KKN Di Kabupaten Pacitan - Mochamad Muflik Kusron; Erhan Bagas Haidar; Fajrin Maulana (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2021)
Corruption, collusion and nepotism (KKN) need to be multidisciplinary, strategic, comprehensive and simultaneous. One of the efforts to prevent corruption is based on involving the formal education department, through courses and learning. The type of research used is descriptive with a qualitative approach. Data was collected using observation and interview techniques. The data analysis technique is using data reduction, data presentation, and conclusion. Efforts to prevent corruption have been carried out in an integrated manner by law enforcement officers and the Government Internal Supervisory Apparatus (APIP). A seminar on corruption in the villages was also held with resource persons from the Police, the Prosecutor's Office and the Inspectorate and the participants were the Chair of the Committee, the Head of the UPT, the Head of the School to the Village Head and other important institutions in the village. Prevention of corruption can be done through: 1) raising public awareness about the destructive impact of corruption, especially for civil servants; 2) anti-corruption education; 3) socialization of criminal acts of corruption through print & electronic media; 4) improvement of civil servant remuneration. This strategy has a good impact in tackling corruption.